An algorithm to personalise the diagnosis of recurrent implantation failure based on theoretical cumulative implantation rate. Issue 6 (27th April 2021) - Rozen, Genia; Rogers, Peter; Teh, Wan Tinn; Stern, Catharyn J; Polyakov, Alex
Abstract: Recurrent implantation failure (RIF) is an imprecisely defined disorder lacking a robust scientific basis. The incomplete understanding of RIF provides significant diagnostic and therapeutic challenges, and a better understanding of the underlying issues is necessary to improve outcomes. We propose a novel concept termed 'Theoretical Cumulative Implantation Rate', the calculation of which is based on objective data, to define whether a patient should be diagnosed with RIF. An updated definition to assist with patient counselling and planning research studies, which is more precise and standardised, is well overdue.